Emergence delirium following sevoflurane anesthesia in adults: prospective observational study - Ramroop,Renair (2019)
Abstract Background and objectives: Emergence delirium after general anesthesia with sevoflurane has not been frequently reported in adults compared to children. This study aimed to determine the incidence of emergence delirium in adult patients who had anesthesia with sevoflurane as the volatile agent and the probable risk factors associated with its occurrence. Design & methods: A prospective observational study was conducted in adult patients who had non-neurological procedures and no existing neurological or psychiatric conditions, under general anesthesia. Demographic data such as age, gender, ethnicity and clinical data including ASA physical status, surgical status, intubation attempts, duration of surgery, intraoperative hypotension, drugs used, postoperative pain, rescue analgesia and presence of catheters were recorded. Emergence delirium intensity was measured using the Nursing Delirium Scale (NuDESC). Results: The incidence of emergence delirium was 11.8%. The factors significantly associated with emergence delirium included elderly age (>65) (p = 0.04), emergency surgery (p = 0.04), African ethnicity (p = 0.01), longer duration of surgery (p = 0.007) and number of intubation attempts (p = 0.001). Factors such as gender, alcohol and illicit drug use, and surgical specialty did not influence the occurrence of emergence delirium. Conclusions: The incidence of emergence delirium in adults after general anesthesia using sevoflurane is significant and has not been adequately reported. Modifiable risk factors need to be addressed to further reduce its incidence.